The Alpine Orogeny in the West and Southwest Iberia Margins. - Terrinha, Pedro (2019)
The Alpine orogeny is well recorded onshore and offshore by tectonic inversion of the Mesozoic rift basins. Large scale linear seamounts (more than 250 km long and with up to 5 km of uplift) involving oceanic and continental lithosphere were carried on top of thrusts, such as the Gorringe seamount and the Estremadura Spur in the SouthWest and West Iberia Margin, respectively. The SouthWest Iberia Margin also recorded the westward migration of the Gibraltar Oceanic slab as the westwards propagation of the Neo-Tethys subduction. Rotation of the tectonic compression from NW-SE to WNW-ESE in Pliocene times caused the development of large scale dextral wrench faults as the present day Africa-Iberia plate boundary. Neotectonics of this plate boundary caused large to mega-scale destructive earthquakes and tsunamis.